Ceruloplasmin‐deficient mice show changes in PTM profiles of proteins involved in messenger RNA processing and neuronal projections and synaptic processes. Issue 1 (17th January 2023) - Villadsen, Birgitte; Thygesen, Camilla; Grebing, Manuela; Kempf, Stefan J.; Sandberg, Marie B.; Jensen, Pia; Kolstrup, Stefanie H.; Nielsen, Helle H.; Larsen, Martin R.; Finsen, Bente
Abstract: Ceruloplasmin (Cp) is a multicopper oxidase with ferroxidase properties being of importance to the mobilisation and export of iron from cells and its ability to bind copper. In ageing humans, Cp deficiency is known to result in aceruloplasminemia, which among other is characterised by neurological symptoms. To obtain novel information about the functions of Cp in the central nervous system (CNS) we compared the brain proteome in forebrains from asymptomatic 4‐6‐month‐old Cp‐deficient (B6N(Cg)‐Cp tm1b(KOMP)Wtsi /J) and wild‐type mice. Of more than 5600 quantified proteins, 23 proteins, were regulated, whereas more than 1200 proteins had regulated post‐translational modifications (PTMs). The genes of the regulated proteins, glycoproteins and phosphoproteins appeared mostly to be located to neurons and oligodendrocyte precursor cells. Cp deficiency especially affected the function of proteins involved in the extension of neuronal projections, synaptic signalling and cellular mRNA processing and affected the expression of proteins involved in neurodegenerative disease and diabetes. Iron concentration and transferrin saturation were reduced in the blood of even younger, 3‐ to 5‐month‐old, Cp‐deficient mice. Iron act as cofactor in many enzymatic processes and reactions. Changes in iron availability and oxidation as consequence of Cp deficiency could therefore affect the synthesis of proteins and lipids. This proteomic characterisation is to our knowledge the first to document the changes taking place in the CNS‐proteome and its phosphorylation and glycosylation state in Cp‐deficient mice. Abstract : In humans, deficiency of the multicopper oxidase and ferroxidase Ceruloplasmin (Cp) leads to neurological symptoms. Proteomics analysis of forebrains from asymptomatic 4‐ to 6‐month‐old Cp‐deficient mice identified >5600 proteins whereof 23 were regulated, and >1200 proteins had regulated post translational modifications, including sialylation of glycopeptides and phosphorylations. The regulated proteins were involved in the KEGG pathway 'neurodegeneration – multiple diseases' and the GO term 'organophosphate biosynthetic process'. The regulated phosphorylated proteins were involved in 'synapse regulation', 'endocytosis', 'microtubule cytoskeleton organisation' and 'mRNA processing'. Changes in iron availability and oxidation resulting from Cp deficiency may be responsible for majority of the proteomic changes.